Pengaruh Debt To Equity Ratio, Return On Equity, Current Ratio, Total Aset Turnover Pada Perusahaan Subsector Food And Beverages Yang Terdaftar Di BEI - Siti Aisyah Nasution; Jelvi Jelvi; Wulandari Wijaya; Lydia Lotan Sephira; Leonita Manurung (Journal of Economic, Bussines and Accounting (COSTING), 2022)
This study aims to analyze the effect of debt to equity ratio, return on equity, current ratio, and total asset turnover on stock prices in the Food and Beverages Subsector Listed on the IDX for the 2017-2020 period. This study uses a quantitative descriptive method. The population of this study is a total of 27 companies and obtained a sample of 19 companies with purposive sampling technique. The analysis technique used was multiple linear regression analysis. The results show that partially, total asset turnover has an influence on stock prices while other variables have no effect on stock prices. The value of the coefficient of determination shows 0.594, which means that 59.4% of the stock price can be explained by independent variables and the remaining 40.6% is explained by other factors but not examined in this study. The conclusion of this study is that only total asset turnover has an effect on stock prices in the food and beverages subsector on the IDX for the 2017-2020 period. Keywords : Debt to Equity Ratio, Return on Equity, Current Ratio, Total Aset Turn Over, Stock Prices